HER2 Codon 655 G-Allele Is Associated With Reductions in Plasma High-Density Lipoprotein Levels in Breast Cancer Patients Treated With Tamoxifen. (1st December 2011) - Chang, Nai-Wen; Chen, Dar-Ren; Chen, Fei-Na; Lin, Chingju; Wu, Chen-Teng
Abstract : Background: Retrospective studies have revealed that overexpression of the epidermal growth factor receptor ErbB-2 (HER2) reduced the efficacy of tamoxifen therapy, which is associated with an increased risk for cardiovascular events. The aim of this study was to evaluate the effects of the HER2 I655V polymorphism (ATC/isoleucine to GTC/valine) on lipid profiles after tamoxifen treatment. Methods: Thirty-four women diagnosed with breast cancer were recruited in the study and followed up for 6 months. The presence of the HER2 I655V polymorphism and fasting plasma lipid profiles before and after tamoxifen treatment were determined for each subject for the duration of the study. Results: In response to tamoxifen therapy, we found that plasma total cholesterol (TC, P = 0.041), low-density lipoprotein-cholesterol (LDL-C, P < 0.001), and high-density lipoprotein-cholesterol (HDL-C, P = 0.012) levels decreased significantly in the A-allele (AA genotype) carriers compared with the baseline measurements. Plasma LDL-C ( P < 0.001) and HDL-C ( P < 0.001) levels decreased significantly, and the TC/HDL-C ( P = 0.027) ratio increased significantly in the G-allele (AG/GG genotypes) carriers. According to the repeated-measures analysis, G-allele carriers had a lower ratio of LDL-C/HDL-C than A-allele carriers did ( P = 0.016). Notably, G-allele carriers had a greater reduction in HDL-C concentration than A-allele carriers ( P = 0.039; G-allele, −12.4 ± 6.8 mg/dL vs A-allele, −5.6 ± 9.5 mg/dL). Conclusions: This study shows that the HER2 codon 655 G-allele was associated with a larger reduction in plasma HDL-C levels in breast cancer patients under tamoxifen therapy. Therefore, we suggest that the polymorphism of HER2 655 codon should be considered for the prevention of cardiovascular events in breast cancer patients after tamoxifen therapy.